Pharmacokinetics and Anti-Tumor Efficacy of PEGylated Liposomes Co-Loaded with Cisplatin and Mifepristone - Karen Ocaña-Arakachi; Julio Martínez-Herculano; Rafael Jurado; Monserrat Llaguno-Munive; Patricia Garcia-Lopez (MDPI AG, 2023)
Although cisplatin is an effective chemotherapy drug used against many types of cancer, it has poor bioavailability, produces severe adverse effects, and frequently leads to tumor resistance. Consequently, more effective formulations are needed. The co-administration of cisplatin with mifepristone, which counters an efflux pump drug-resistance mechanism in tumor cells, has shown important synergism, but without resolving the problem of poor bioavailability. Specificity to tumor tissue and bioavailability have been improved by co-encapsulating cisplatin and mifepristone in a liposomal formulation (L-Cis/MF), which needs further research to complete pre-clinical requirements. The aim of this current contribution was to conduct a pharmacokinetic study of cisplatin and mifepristone in male Wistar rats after administration of L-Cis/MF and the conventional (unencapsulated) formulation. Additionally, the capacity of L-Cis/MF to reduce tumor growth in male nude mice was evaluated following the implantation of xenografts of non-small-cell lung cancer. The better pharmacokinetics (higher plasma concentration) of cisplatin and mifepristone when injected in the liposomal versus the conventional formulation correlated with greater efficacy in controlling tumor growth. Future research on L-Cis/MF will characterize its molecular mechanisms and apply it to other types of cancer affected by the synergism of cisplatin and mifepristone.